Assessing Industry Risk by Ratio Analysis: A Reply. - Falk, Haim; Heintz, James A. (The Accounting Review, 1978)
B & C have raised a number of important points regarding our original paper. Many of the issues were addressed in the original paper so that our response to them here necessarily has been some- what repetitious of the previous discussion. Nevertheless, we are grateful to B & C for pointing out some potential difficulties in applying the technique, for emphasizing the need for validation before the technique can be of practical value, and for giving us the opportunity to clarify and expand upon numerous issues which possibly were not dealt with satisfactorily in the original paper.